Hippo-warts-yorkie pathway is crucial for larval survival and shell development in Pacific abalone (Haliotis discus hannai) - Rui Xue; Dinglong Yang; Gao Fang; Tianyu Zhang; Xiaohan Liu; Zhijun Dong; Xiangquan Liu; Xiaojing Li; Jianmin Zhao (Comparative Immunology Reports, 2024)
Hippo pathway coordinate developmental processes through regulating cell growth, proliferation and programmed death. However, mollusks achieved little focus so far on the role of this significant pathway during larval development. In this study, three core genes, hippo, warts and yorkie, were identified in Haliotis discus hannai. They mainly expressed at trochophore and veliger stages. Positive signals of yorkie occurred near the edge of shell field at the trochophore stage (12 and 15 hpf), then tended to overlap with hippo and warts (18 hpf). In veliger larva after torsion (at 30 hpf), their expression appeared in several non-overlapping areas. These findings suggested their important roles in post-embryonic development. Silencing of yorkie led to 90 % cumulative mortality at 60 h posttreatment, with a 33 %-highest abnormality rate, meanwhile significantly upregulated the relative expression of hippo and warts at 6 h and 12 h posttreatment (P < 0.05). A smaller shell was the most common abnormal type and also a common feature among three abnormal types related to RNA interfere. Besides, the reduction rate of shell area in survival larvae trended to reduce from 18 h to 48 h posttreatment. These findings proved a crucial role of yorkie in larval survival and shell development. Our findings would help to better understand the potential role of Hippo pathway, especially its roles in the development of abalone larva.